Innovative Education: Public-Private Partnership for Developing International Trading Talent - Kumar, Ravi; Seng, Tan Boon (Journal of Strategic Innovation and Sustainability, 2018)
The education sector is often criticized for the growing gap between what business needs and what education provides. This paper discusses an innovative use of tripartite public-private partnership (PPP) of the government, university and industry partners to design, build, operate and finance the delivery of the international trading program () in Nanyang Technological University (NTU) as a complement to the contracting model of government provision and university production of education. The program operation is institutionalized with a centre of excellence and its advisory board. A corporate partnership scheme provides the financial foundation and industry commitment to ensure program sustainability.